2015
DOI: 10.1016/j.energy.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Solar fuel processing efficiency for ceria redox cycling using alternative oxygen partial pressure reduction methods

Abstract: a b s t r a c tSolar-driven non-stoichiometric thermochemical redox cycling of ceria for the conversion of solar energy into fuels shows promise in achieving high solar-to-fuel efficiency. This efficiency is significantly affected by the operating conditions, e.g. redox temperatures, reduction and oxidation pressures, solar irradiation concentration, or heat recovery effectiveness. We present a thermodynamic analysis of five redox cycle designs to investigate the effects of working conditions on the fuel produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 33 publications
6
47
0
Order By: Relevance
“…The trade-off between fuel purity and fuel yield is intrinsic to the dynamics of the oxidation step; optimization will be contingent upon the downstream processing of the fuel and the economics of the entire solar plant. As anticipated by thermodynamic analyses, 31,32 increasing the mass flow rate of the inert gas affected negatively Z solar-to-fuel because both Q inert and Q pump increased monotonically with : V Ar and additional energy was wasted for heating a larger Ar flow to the desired T reduction (ref. 50, Fig.…”
Section: Resultsmentioning
confidence: 83%
“…The trade-off between fuel purity and fuel yield is intrinsic to the dynamics of the oxidation step; optimization will be contingent upon the downstream processing of the fuel and the economics of the entire solar plant. As anticipated by thermodynamic analyses, 31,32 increasing the mass flow rate of the inert gas affected negatively Z solar-to-fuel because both Q inert and Q pump increased monotonically with : V Ar and additional energy was wasted for heating a larger Ar flow to the desired T reduction (ref. 50, Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Some prior works [8,12] only considered a mixed gas system instead of a counter-flow arrangement, and the much higher inert gas flowrates calculated in this way tend to show that vacuum reduction is more efficient, even with limited pump efficiency values [12]. Other works compared counter-flow to perfect mixing [14] and parallel-flow [15,16] arrangements, and showed that the counter-flow was more efficient, but suggested that the final flow arrangement would be an intermediate state.…”
Section: Introductionmentioning
confidence: 99%
“…Others have suggested recycling inert gas, rather than producing it in an open-loop fashion [15,18]. Still others have suggested using both an inert sweep gas and vacuum pumping simultaneously [14]. In addition to the direct study of inter gas sweeping, other works have compared the energy required for inert gas and vacuum [14,19].…”
Section: Introductionmentioning
confidence: 99%
“…The above relationship, Eq. (38), was also implemented in [45]. In the present work, we also use Eq.…”
Section: Simulation Results For the Uf 10 Kw Solar Reactormentioning
confidence: 99%